Pelatihan Pembuatan Pupuk Bokasi dari Dedaunan Kering Dikelompok Tani Wanita Cerdas Desa Lawelu, Kecamatan. Ulu Moro'o, Kabupaten. Nias Barat - Tuti Ariani Bawamenewi; Fitri Julianti Gea; Richard Alexander Waruwu; Destri Natalis Harefa; Helmin Parida Zebua (Lembaga Pengembangan Kinerja Dosen, 2025)
Agriculture is the economic backbone of the people of Lawelu Village, Ulu Moro'o District, West Nias Regency, but dependence on chemical fertilizers is a serious challenge that threatens the sustainability of production. In response to this, training on making bokasi fertilizer based on local dry leaves has been carried out to increase the capacity of members of the